Implementation of Independent Curriculum in Biology Learning at State Senior High School 3 Poso - Samaela, Dewi Purwasih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The independent curriculum is one of the curricula that can be utilized by educational units to return learning from the 2022–2023 academic year to the 2024–2025 academic year. Inadequate infrastructure and facilities, such as unfinished laboratories and libraries and uncertain internet access, are other elements that hinder the implementation of the independent curriculum. This study aims to examine in more depth the implementation of the Independent Curriculum at SMA N 3 Poso. This study uses a qualitative approach with teachers and students as research subjects. This study was planned using a case study methodology. The results of the study indicate that the independent curriculum at SMA Negeri 3 Poso has been implemented as well as possible. Teachers continue to use the RPP and assessments set by the Ministry of Education, Culture, Research, and Technology in the classroom. The Learning Implementation Plan (RPP) has focused on students, is efficient, and effective. Despite using various learning strategies, teachers remain primarily responsible for supervising student actions during the learning process. Utilization of the Pancasila student profile which emphasizes critical and creative thinking, mutual cooperation, and noble morals. Formative and summative assessments are used in learning evaluation. Overall, it can be said that the implementation of the independent curriculum at SMA Negeri 3 Poso is in accordance with the laws and regulations set by the government.